Sztuka Tajemnicy. „Metafantastyka” albo teoria literatury fantastycznej Stefana Grabińskiego - Knap, Jakub (Przestrzenie Teorii, 2023)
The subject of the article is a pioneering in Poland critical conception of the fantastic developed by highly esteemed prewar author of the fantastic literature, Stefan Grabiński. The crucial, remarkable comments referring to fantastic literature were comprised by Grabiński in his extensive essay entitled On fantastic literature. The dissertation in question was never published in whole, however, to find its issue while his life in merely two short parts of it in press edition. In the first part of the article the archival documents were used (mainly the letters) which enabled the reconstruction of puzzling history of the manuscript of said essay now probably lost forever. In the second part, basing on the published parts of the essay, as well as other critical statements of the Polish writer, the main aspects of Grabiński’s theory were discussed. Upon the profound analyses made therefrom it appeares that Grabiński perceived and gave the fantastic genre a unique meaning and value, notably owing to its specific privileged language exposing metaphysical expression of the Mystery. The writer managed to depict in accurate, innovative and convincing way the character of fantastic literature, both in terms of historical and anthropological origin of this kind of literary creativity, and its aesthetics, social and philosophical attributes what makes these researchers innovative and even anticipativewith reference to the corresponding studies of postwar literature theoreticians of fantastic genre (e.g. L. Vax, R. Caillois, T. Todorov). Discursive statements on the issue of fantastic literature of Grabiński are further related to much wider phenomenon which was focused on developing critical analysis of fantastic literature in Poland in the first decades of the twentieth century.